2010
DOI: 10.1126/science.1179044
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Ribosomal RNA Gene Copies Maintains Genome Integrity

Abstract: The ribosomal RNA (rDNA) gene repeats are essential housekeeping genes found in all organisms. A gene amplification system maintains large cluster(s) of tandemly repeated copies in the chromosome, with each species having a specific number of copies. Yeast has many untranscribed rDNA copies (extra copies), and we found that when they are lost, the cells become sensitive to DNA damage induced by mutagens. We show that this sensitivity is dependent on rDNA transcriptional activity, which interferes with cohesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
290
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(313 citation statements)
references
References 20 publications
18
290
5
Order By: Relevance
“…TOR inhibition can alter the rate of marker loss from the rDNA (23, 24); however, this occurs through the BIR pathway, which acts primarily to homogenize rDNA sequences, and it is not clear why rDNA homogenization should respond to the environment. In contrast, cells with suboptimal rDNA copy number are forced to up-regulate RNA pol I transcription to maintain ribosome synthesis, and rDNA amplification is a logical response in this situation; although ribosome synthesis can be enhanced temporarily by increasing RNA pol I transcription, this strategy is harmful in the long term (22,40). Controlled rDNA amplification is therefore a response to available nutrients being in excess compared with ribosome synthesis capacity.…”
Section: Discussionmentioning
confidence: 99%
“…TOR inhibition can alter the rate of marker loss from the rDNA (23, 24); however, this occurs through the BIR pathway, which acts primarily to homogenize rDNA sequences, and it is not clear why rDNA homogenization should respond to the environment. In contrast, cells with suboptimal rDNA copy number are forced to up-regulate RNA pol I transcription to maintain ribosome synthesis, and rDNA amplification is a logical response in this situation; although ribosome synthesis can be enhanced temporarily by increasing RNA pol I transcription, this strategy is harmful in the long term (22,40). Controlled rDNA amplification is therefore a response to available nutrients being in excess compared with ribosome synthesis capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this finding, the copy number of rRNA genes in S. japonica seems not very appropriate for its genome size of about 545 Mb (Ye et al 2015), although the copy number still stands within the range of the available data from algae (Table 3). In these studies on the estimation of yeast rRNA gene copy number, Ide et al (2010) and Kobayashi (2011) found that the loss of these repeats in yeast cells confers sensitivity to DNA damage caused by mutagens such as UV radiation. Taking this into consideration and the fact that S. japonica can survive under medium irradiance of no more than 30% of the water surface solar irradiance (Fei et al 1989), which is generally accepted as the result of natural selection and adaptation to low light in the sub-littoral region (Häder and Figueroa 1997), the low copies of rDNA serves as a possible explanation why this particular kelp species is unable to tolerate high irradiance.…”
Section: Discussionmentioning
confidence: 99%
“…Flanking sequences of the non-functional insert suggest that the insertion occurred in a 26S ribosomal RNA (rRNA) gene. Since rRNA genes are present in several copies in the genome (Ide et al, 2010), disruption of a single copy is unlikely to have an effect on the characteristics of the plant.…”
Section: Summary Of the Previous Evaluation Of Event Mon 531 Includimentioning
confidence: 99%